Neoliberalismo Crisis Actual - Peck, Jamie (Documentos y Aportes en Administración Pública y Gestión Estatal, 2012)
The article discuss the characteristic of the current neoliberalism to understand it as a changeable and complex project whose economic and political sustainability is continuously reinvented and whose governance and spatiality is in need of being understood differently, if a viable alternative is to be constructed. Taking the recent neoliberal crisis as a point of departure, it discusses three main and interrelated aspects: firstly, the polymorphic characteristics of neoliberalism as a process in transformation; secondly, the way in which it could be acted against this neoliberal process by bringing some contributions from Polanyi back into the analysis so as to understand neoliberalism's dynamics; thirdly, the characteristics of some current policies taking place under neoliberal process, some of which could became viable alternatives in the long term. (English)
Geography
Keywords: 21st century; POLANYI; Karl; 1886-1964; crisis; economic history; global financial crisis; 2008-2009; neoliberalism; neoliberalismo; political philosophy; political practices; practical politics; prácticas políticas; world politics - economic aspects

Textos escogidos. Karl Polanyi - Coraggio, J.L. (Buenos Aires : Consejo Latinoamericano de Ciencias Sociales (CLACSO) ; Los Polvorines, Provincia de Buenos Aires : Universidad Nacional de General Sarmiento, 2012)
Contents of book: Primera parte: Karl Polanyi y su obra: Actualidad de Karl Polanyi / Jean-Louis Laville. Karl Polanyi : su vida y época / Marguerite Mendell y Kari Polanyi Levitt. Karl Polanyi y la otra economía en América Latina / José Luis Coraggio – Segunda parte: Los ensayos de Karl Polanyi: El lugar de las economías en las sociedades (1957) ; La economía como proceso instituido (1957) ; Aristóteles descubre la economía (1957) ; Feudalismo primitivo y feudalismo de la decadencia (1950) ; Marxismo e historia económica (comentario a Maurice Dobb) (1947) ; Comerciantes y comercio (1951) ; Semántica de los usos de la moneda (1957) ; Economía y democracia (1932) ; La esencia del fascismo (1935). El fascismo y la terminología marxista (1934) ; El marxismo redefinido (1934) ; Marx sobre el corporativismo (1934-1937) ; El cristianismo y la vida económica (1934-1937) ; Comunidad y sociedad : la crítica cristiana a nuestro orden social (1937) ; ¿Capitalismo universal o planificación regional? (1945) ; El significado de la democracia parlamentaria (1944-1945) ; Nuestra obsoleta mentalidad de mercado (1947) ; Sobre la creencia en el determinismo económico (1947) ; Jean-Jacques Rousseau o ¿Es posible una sociedad libre? ; La libertad y la tecnología (1955) ; La máquina y el descubrimiento de la sociedad (1957) ; La libertad en una sociedad compleja (1957) ; La sociedad opulenta según Aristóteles (1959).
Economics
Keywords: antropología económica; economic anthropology; economic history; economics; economía; historia económica